Fenomena Hate Speech dan Runtuhnya Keadaban Kultural - Winarto Eka Wahyudi (Proceedings of Annual Conference for Muslim Scholars, 2017)
Since the easier access to digital technology based information everyone is free to interpreted and argue for all kinds of phenomena that occur. Issues about politics, education, economics to the most private aspect (read: religion), not escape from public interpretation. This reality certainly has implications on two aspects that are contradictory. This is because the community digests the information it obtains in varied ways, because it departs from the tendency of insight and its preference to certain primordial entities. The logical consequence of this reality is that, on the one hand, the information successfully absorbed by the public has spawned a generation of societies that significantly shapes a higher reading culture, albeit at a glance and a deep level. But on the other hand, the impact of this accessible information access spawned the latah generation, whose knowledge modality through cyberspace feels legitimate to give opinions and interpretations of everything. In this position emerged the seeds of disputes that could lead to social divisions. Nowadays, social media is becoming the lifestyle of society so distancing access to information from the public is not good. There needs to be an in-depth study on the use of digital information appropriately so that the cultural richness of the Indonesian nation does not collapse due to the misuse of social media as a provocative instrument for the fragmentation of the nation's culture.